Giant desmoplastic small round cell tumor of the abdomen: A case report - Wang, Wuke; Chen, Yunjie; Wang, Chunnian; Su, Hui (Frontiers in Oncology, 2022)
BACKGROUND Desmoplastic small round cell tumor (DSRCT) is a rare, aggressive, mesenchymal malignancy of a separate clinicopathological entity. It has a predilection for young men, with no evidence of any ethnic predilection. The current diagnostic gold standard for DSRCT includes histopathologic, immunohistochemical, and cytogenetic studies in order to confirm the variable phenotypic expression and characteristic chromosomal translocation. CASE SUMMARY A 65-year-old male presented with a sensation of an abdominal mass and a presentation of an incomplete bowel obstruction. Initial lab tests were in the normal ranges except carbohydrate antigen. Contrast-enhanced CT showed a large, mass confounding density was occupied in the omentum majus area of the middle and lower abdominal wall. A 3D reconstruction of the images was performed to clarify the relationship between tumor and colon, and a colonoscopy confirmed. After surgery， Immunohistochemistry and Fluorescence in situ hybridization (FISH) revealed EWSR1-WT1 gene rearrangement at 22q12, confirming the diagnosis of desmoplastic small round cell tumor CONCLUSION Being differ from the predilection of DSRCT for young men, the patient in our case is a 65-year-old male, with a huge mass involving the transverse colon and the bladder.